2014
DOI: 10.1002/ana.24171
|View full text |Cite
|
Sign up to set email alerts
|

Normobaric hypoxia and symptoms of acute mountain sickness: Elevated brain volume and intracranial hypertension

Abstract: The data provide the strongest evidence to date to support the hypothesis that the "random" nature of AMS symptomology is explained by a variable intracranial pressure response to hypoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 30 publications
4
54
1
Order By: Relevance
“…The measurement of ONSD seems to simply reflect a general rise in brain volume in subjects exposed to hypobaric hypoxia11. Despite that no direct comparison between brain volume, ICP and ONSD in hypobaric hypoxia has been made so far, a relative increase in ICP (although within the normal range) is suggested by the increase in grey and white matter volumes (and a decreased in CSF) after 10 and 22 h of normobaric hypoxia in MRI studies2930. The same effect on ICP was suggested by different in-field studies with other neuroimaging techniques11.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of ONSD seems to simply reflect a general rise in brain volume in subjects exposed to hypobaric hypoxia11. Despite that no direct comparison between brain volume, ICP and ONSD in hypobaric hypoxia has been made so far, a relative increase in ICP (although within the normal range) is suggested by the increase in grey and white matter volumes (and a decreased in CSF) after 10 and 22 h of normobaric hypoxia in MRI studies2930. The same effect on ICP was suggested by different in-field studies with other neuroimaging techniques11.…”
Section: Discussionmentioning
confidence: 99%
“…16 Association between change in ICP and headaches was also recently reported in a study of acute mountain sickness, where severity of headaches was shown to be proportional to the hypoxia-induced increase in ICP as measured by MRICP. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Total brain volume increased on average 59 ml involving mostly gray matter volume after 10 hours in hypoxia (Lawley et al, 2014). Intracranial pressure (ICP) was estimated non-invasively by an MRI method that had been validated in baboons and some humans.…”
Section: Mri Study Suggests Increased Brain Volume and Intracranial Pmentioning
confidence: 99%